(untitled) (American Journal of Islam and Society, 2009)
Using classical and current definitions of jihad and theories of globalization and neoliberalism, this essay discusses jihad and current jihadist movements within their reactive and responsive relationships to the material conditions of the Islamic world in general and of Pakistan in particular. Written in response to the essentialist claims of American neoconservative scholars, it suggests that jihadist militancy is not inherently Islamic, but rather a product of the material political conditions created by the Muslim colonial experience and perpetuated by the destabilizing influence of power politics, neoliberal capital, and the failure of the national promise of the postcolonial Muslim nation-states.